Personality Factors as Antecedents in Social Capital of Students (Indian Journal of Extension Education, 2020)
Social capital has been widely discussed across various social sciences research streams, development agencies and research institutions. The study examines personality factors as antecedents of student social capital. The study aimed to check whether the network of relationships among students who study with each other (i.e. social capital) which help in enabling students to work together is affected by personality and various other demographic factors like gender, age, educational qualification, family income and residential status etc. A survey was conducted to collect data from 180 students of various departments of two educational institutes (NIT Kurukshetra and Kurukshetra University) that identified a number of factors like; bonding with friends, acceptance of system, support & cooperation, selfishness and harmony as social capital. PCA, t-test and One way ANOVA were used to draw inferences. The findings revealed that age, educational qualification, family income and residential status all contributes to affect social capital of students in addition to personality factor. Extroverted students tend to make more friends. The study also analyzed social networks in the classrooms and concludes that educators should put themselves in a position to better understand the social context in which their students operate. In order to appreciate and cultivate the way students interact with each other, educators should Access and management of the students’ personality factors can lead to success as individuals and in group settings.